'Time is Money': Dar es Salaam's Daladala Inscriptions and the Ethics of Everyday. Issue 4 (2nd October 2021) - Wakota, John
ABSTRACT: In Dar es Salaam, privately-owned minibuses, known as daladalas, are the most popular means of commuting. Their routes crisscross the city and the minibuses themselves are adorned with messages and inscriptions on their rear bumpers. These inscriptions comment on aspects of city life, forming a significant corpus of urban scripts. Three main categories emerge from this corpus: work, money and time. In this paper, I show how these three categories are intimately connected and can be read as an intertextual body of urban scripts commenting on the ethics of everyday life in the city. Reading these inscriptions as authorless texts, produced and interpreted by the city, I examine how they offer a nuanced yet ambivalent representation of Dar es Salaam. The three themes act as nodes around which images of and metaphors for city life in Dar es Salaam are articulated. This paper sheds light on how we can read these pithy and ubiquitous texts as an archive which comments upon what it means to live in Dar es Salaam and the ethics of city life.